Beyond the inert doublet: imprints of Scotogenic Yukawa interactions at FCC-ee - Carlo Marzo; Aurora Melis (European Physical Journal C: Particles and Fields)
Abstract It is tempting to interpret the minuscule scale of neutrino masses as a symptom of its radiative origin. In light of the notable leap in precision expected at the Future Circular Collider, we explore areas of the parameter space that can simultaneously support the detectable Higgs-strahlung signal with parallel ones from forthcoming measurements in low-energy observables. We pinpoint the role that the extra fermions have in shaping a signal distinct from the pure Inert Doublet one. The details of the full one-loop computation and on-shell renormalization are presented. Both normal and inverted hierarchies for the radiatively generated neutrino masses and angles are investigated.